Effect of partially replacing concentrate mix with hot water- and polyethylene glycol-treated Prosopis juliflora leaf meal on the feed intake, digestibility, body weight gain, and carcass characteristics of Arsi-Bale sheep fed a grass hay-based diet - Belete, Sisay; Tolera, Adugna; Betsha, Simret; Dickhoefer, Uta (Frontiers in Animal Science, 2026)
This study evaluated the effects of replacing a concentrate mix with hot water- and polyethylene glycol-treated Prosopis juliflora leaf (PJL) meal on the feed intake, digestibility, nitrogen balance, body weight gain, and carcass characteristics of Arsi-Bale sheep fed a grass hay-based diet. A total of 30 male sheep (initial body weight of 20.7 ± 1.6kg) were blocked into six groups and allocated to diets in which the concentrate mix was substituted with PJL meal at 0% (PJL0), 5% (PJL5), 10% (PJL10), 15% (PJL15), and 20% (PJL20). The experiment consisted of 84-day feeding and 10-day digestibility and nitrogen balance trials, which ended with carcass evaluation. Data were analyzed using general linear model (GLM) followed by polynomial contrast analysis using SAS (ver. 9.4). The intake of dry matter (DM), organic matter (OM), crude protein (CP), metabolizable energy (ME), neutral detergent fiber (NDF), and acid detergent fiber (ADF) decreased linearly and quadratically (p < 0.05) when the level of substitution with PJL meal increased. The least intake was observed when the PJL replacement of the concentrate mix exceeded 15%. The apparent digestibility of DM, OM, and CP was significantly (p < 0.05) higher in the PJL5 than in the PJL20 group. The daily nitrogen intake, urinary nitrogen loss, and nitrogen retention of the sheep decreased quadratically (p < 0.05) as the proportion of PJL meal increased. The daily nitrogen intake and retention were significantly lower (p < 0.05) in PJL20 compared with others. The urine nitrogen excretion was higher (p < 0.05) in PJL5 than that in PJL20. The average daily weight gain (ADG) of the sheep decreased linearly and quadratically, whereas the feed conversion efficiency (FCE), hot carcass weight, and slaughter body weight-based carcass dressing percentage dropped linearly (p < 0.001) when the substitution level increased. Substituting the concentrate mix with up to 15% PJL meal did not negatively affect the feed intake, apparent digestibility, or production performance of Arsi-Bale sheep. However, higher inclusion levels (20%) resulted in a reduced feed intake and weight gain and also showed a tendency for reduced digestibility. Further studies should assess the long-term effects and economic viability of treated PJL meal as an alternative feed ingredient in ruminants.